Water supply and demand in the Yellow river basin: Opportunities from Water Savings - Xu, Zongxue; Yongfeng, Fu; Cheng, Lei; Yongliang, Sun; Zhu, Tingju; Jingzong, Li (International Food Policy Research Institute, 2010)
The second longest river in China after the Yangtze, the Yellow River and its basin (YRB) is the breadbasket of China and the cradle of Chinese civilization. With only 2 percent of national water resources, the basin generated 14 percent of Chinese grain production and 14 percent of the country's GDP in 2000.